2019
DOI: 10.5194/acp-19-6949-2019
|View full text |Cite
|
Sign up to set email alerts
|

Vertical observations of the atmospheric boundary layer structure over Beijing urban area during air pollution episodes

Abstract: Abstract. We investigated the interactions between the air pollutants and the structure of the urban boundary layer (UBL) over Beijing by using the data mainly obtained from the 325 m meteorological tower and a Doppler wind lidar during 1–4 December 2016. Results showed that the pollution episodes in this period could be characterized by low surface pressure, high relative humidity, weak wind, and temperature inversion. Compared with a clean daytime episode that took place on 1 December, results also showed th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 81 publications
1
33
0
Order By: Relevance
“…In addition, some specific synoptic patterns might also cause noticeable changes in both UHII and PM 2.5 . Synoptic patterns can affect air quality episodes which are already expressed through the meteorological variables (e.g., temperature, wind speed, rainfall, and cloud cover), and thus, these variables can represent a certain synoptic situation over a given region (Kassomenos et al, ; Luo et al, ; Miao et al, , ; Ning et al, , ; Shahgedanova et al, ; Wang, Liu, et al, ; Yang Yim et al, ; Zheng et al, ). The possibly different associations between the UHII and PM 2.5 under different synoptic patterns will be the focus of a future study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some specific synoptic patterns might also cause noticeable changes in both UHII and PM 2.5 . Synoptic patterns can affect air quality episodes which are already expressed through the meteorological variables (e.g., temperature, wind speed, rainfall, and cloud cover), and thus, these variables can represent a certain synoptic situation over a given region (Kassomenos et al, ; Luo et al, ; Miao et al, , ; Ning et al, , ; Shahgedanova et al, ; Wang, Liu, et al, ; Yang Yim et al, ; Zheng et al, ). The possibly different associations between the UHII and PM 2.5 under different synoptic patterns will be the focus of a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Many observations in Beijing found that meteorological conditions are a main driver on both the onset and longevity of haze. Large scale synoptic conditions such as southerly winds and low pressure often preempt pollution episodes which tend to occur every 4-7 days in Beijing wintertime (Liu et al, 2018a;Wang et al, 2019). These conditions are associated with the beginning of 'haze' as the switch in meteorological conditions from strong northwesterly to southerly winds advects pollution from surrounding provinces into Beijing.…”
Section: Sensitivity To Meteorologymentioning
confidence: 99%
“…conditions such as temperature inversions, increased humidity and decreased wind speed (Dou et al, 2015;Zhang et al, , 2017Wang et al, 2019;Zhong et al, 2019b).…”
mentioning
confidence: 99%
“…Research examining the feedback effect on Beijing haze episodes has thus far relied upon observations or regional modelling studies. Q. , Zhong et al (2018b), Gao et al (2015) and Wu et al (2019) performed model simulations of pollution episodes using the Weather Research and Forecasting model with added chemistry (WRF-Chem) to examine the feedback effect. Their results all confirm that aerosol-radiation interactions, aerosol hygroscopic growth and aqueous heterogeneous reactions are all factors in the suppression of boundary layer development and result in increased surface PM 2.5 concentrations during polluted episodes in the North China Plain.…”
Section: Introductionmentioning
confidence: 99%